GDP-Fucose Uptake into the Golgi Apparatus during Xyloglucan Biosynthesis Requires the Activity of a Transporter-Like Protein Other Than the UDP-Glucose Transporter - Wulff, Cristian (American Society of Plant Biologists, 2000)
The molecular mechanisms regulating hemicelluloses and pectin biosynthesis are poorly understood. An important question in this regard is how glycosyltransferases are oriented in the Golgi cisternae, and how nucleotide sugars are made available for the synthesis of the polymers. Here we show that the branching enzyme xyloglucan α,1–2 fucosyltransferase (XG-FucTase) from growing pea (Pisum sativum) epicotyls was latent and protected against proteolytic inactivation on intact, right-side-in pea stem Golgi vesicles. Moreover, much of the XG-FucTase activity was membrane associated. These data indicate that XG-FucTase is a membrane-bound luminal enzyme. GDP-Fuc uptake studies demonstrated that GDP-Fuc was taken up into Golgi vesicles in a protein-mediated process, and that this uptake was not competed by UDP-Glc, suggesting that a specific GDP-Fuc transporter is involved in xyloglucan biosynthesis. Once in the lumen, Fuc was transferred onto endogenous acceptors, including xyloglucan. GDPase activity was detected in the lumen of the vesicles, suggesting than the GDP produced upon transfer of Fuc was hydrolyzed to GMP and inorganic phosphate. We suggest than the GDP-Fuc transporter and GDPase may be regulators of xyloglucan fucosylation in the Golgi apparatus from pea epicotyls.